Fungal endophytes from salt-adapted plants confer salt tolerance and promote growth in wheat (Triticum aestivum L.) at early seedling stage. Issue 8 (9th August 2022) - N, Manjunatha; Manjunatha, Nayana; Li, Hua; Sivasithamparam, Krishnapillai; Jones, Michael G.K; Edwards, Ian; Wylie, Stephen J.; Agarrwal, Ruchi
Abstract : With increasing human global population, increased yield under saline conditions is a desirable trait for major food crops. Use of endophytes, isolated from halophytic hosts, seems to be an exciting approach for conferring salt tolerance to a salt-sensitive crop. Therefore, in the current study, fungal endophytes were isolated from halophytic plants' roots and their ability to withstand in vitro salt stress was evaluated. The fungal endophytes could withstand up to 1M NaCl concentrations and this tolerance was independent of their host or tissue source. When inoculated on salt-sensitive wheat seeds/seedlings, several of the endophytes showed a positive impact on germination and biomass-related parameters upon salt stress, both in vitro and under glasshouse conditions. One of the isolates from dicot plants (identified as Microsphaeropsis arundinis ) could successfully colonize wheat and promote its growth under salt and no-salt conditions. Amongst the fungal isolates that are known to be natural endophytes of wheat, Chaetomium globosum was the best performing isolate and has previously been reported to be an effective biocontrol agent. Based on the results of our preliminary study, we suggest that these fungal endophytes could prove beneficial for enhancing the salt stress tolerance of wheat crop.